The Effect of Motivation on Employee Performance Through Employee Satisfaction of The Tax Office in Surakarta - Dodik Jatmika; Mardiana Andarwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
The purpose of this study is to find the effeect of motivation on employee performance through employee satisfaction of the tax office in Surakarta. The population of this study totaled 107 employees and all serve as a sample research. The result of research shows that (1) the motivation influential on satisfaction of employees, (2) the motivation does not influence on the performance of employees, (3) satisfaction work influential on the performance of employees, and (4) the motivation influential on the performance of employees through satisfaction work employees in Pratama Surakarta tax service office. Keywords: Motivation, satisfaction and performance